Deployment and Evaluation of a Multi-Hop Wireless Network - Idris, Fakrulradzi; Hashim, Norlezah (IJCTT, 2013)
Multi-hop wireless network uses two or more wireless hops to send information from source to destination. This paper presents the design and deployment of multi-hop wireless network testbed in Universiti Teknikal Malaysia Melaka (UTeM). While using the testbed to provide additional WiFi coverage around the cafeteria area in UTeM Industrial Campus, real-time measurements of various key parameters are carried out. This paper also provides some technical details of the testbed implementation as well as performance evaluation of network coverage, signal strength and connectivity. Performance of network throughput and effect of difference channel allocations are also presented.